Public agriculture investment and food security in ECOWAS - Kamenya, Madalitso A.; Hendricks, Sheryl L.; Gandidzanwa, Colleta; Ulimwengu, John M.; Odjo, Sunday P. (Elsevier, 2022)
Public agriculture expenditure is a significant growth catalyst. However, evaluating the impact of public agriculture expenditure on food security remains scanty. This paper assessed the impact of public expenditure on food security in nine ECOWAS countries using four indicators of food security, one in each dimension (availability, access, utilization and stability). Using a fixed-effect generalized least squares model the study found that public agricultural expenditure has improved. However, this has not translated to an automatic improvement in food security. The levels of stunting and undernourishment were still high in the nine ECOWAS countries. A one-unit increase in public agriculture expenditure was associated with a 0.2% reduction in undernourishment andan improved average dietary energy supply adequacy between 2000 and 2016. The paper concluded that the nine ECOWAS countries have made considerable progress in improving food availability, that public agriculture expenditure by share has increased in the nine ECOWAS countries since the inception of CAADP, with several countries meeting the 10% target of spending on agriculture for several years and that public agricultural expenditure had a positive impact on food accessibility and availability. The analysis could be replicated in the design of national food security investment plans and help identify strategies to accelerate food security and nutrition improvements in African countries.